Validação do critério ISSF aplicado a juntas adesivas usando métodos numéricos - Dionísio, João Manuel Maia (2022)
Due to the limitations presented by conventional joining techniques, like bolted and welded joints, the industry has turned attention to adhesively-bonded joints. The lower weight and decreased stress concentrations are some of the advantages made possible by this technique. Over the years, diverse analytical and numerical approaches to the failure of these joints were investigated. The work presented in this report aims to propose and validate a fracture mechanics based approach to joint failure, named Intensity of Singular Stress Fields (ISSF). With this purpose, aluminium and composite single-lap joints bonded with a brittle adhesive were tested. Different overlap lengths (LO) were also considered in order to evaluate this parameter influence in the final results. The experimental data was treated and the average maximum loads sustained by the joints were collected. Then, a numerical method for joint strength prediction was proposed, consisting of a combination of experimental and numerical information. The numerical data was obtained through simulations resorting to the Finite Element Method (FEM) and a meshless technique, the Radial Point Interpolation Method (RPIM). The validation of the approach was achieved by analysing the polar stress components and comparing the experimental and numerical results. It was experimentally verified that increasing LO leads to an increase in strength of the joints. The proposed technique was successfully applied for both aluminium and composite adherends even though they had different formulations. The results attained with the proposed method were promising given itssimplicity compared with previously proposed methodologies. The method’s application to meshless methods was also confirmed since the RPIM presented very similar results to the FEM, despite presenting some oscillations.